Environmental impact of cereal straw management: An on-farm assessment. (20th January 2017) - Palmieri, N.; Forleo, M.B.; Giannoccaro, G.; Suardi, A.
Abstract: This work assessed the environmental impact of cereal straw end-practices at farm gate and highlighted the best on-farm scenario. A sample of cereal farms located in Apulia Region, in Southern Italy, was investigated through a survey questionnaire. Straw incorporation in the soil, straw burning and baling, were the three practices considered. In the light of the ever-growing demand of straw for energy feedstock production, we discussed two scenarios, namely the status quo and the demand pulled scenarios, each one with a different mix of the three straw end-practices. Following farmer's intentions, in the demand pulled scenario a high percentage of straw was baled while reducing straw incorporation; straw burning practice was not eliminated because it allows farmers to prepare the soil for cultivation. Sensitivity analysis tested different wheat and straw allocation methods (economic vs mass and cereal unit allocation). The environmental impact of alternative straw end-practices and scenarios was assessed by means of an attributional Life Cycle Assessment. Straw incorporation resulted the best environmental practice. Scenarios had quite similar impacts for 8 out of 11 impact categories, but the demand pulled scenario was less impacting than the status quo on global warming, human toxicity, and photochemical oxidation impact categories. These results allow us to conclude that the perspective of selling the straw on the local market for energy production is a better solution compared to the current situation.